Do Children Who Move Home and School Frequently Have Poorer Educational Outcomes in Their Early Years at School? An Anonymised Cohort Study - Hutchings, Hayley A. (Public Library of Science, 2013)
Frequent mobility has been linked to poorer educational attainment. We investigated the association between moving home and moving school frequently and the early childhood formal educational achievement. We carried out a cohort analysis of 121,422 children with anonymised linked records. Our exposure measures were: 1) the number of residential moves registered with a health care provider, and 2) number of school moves. Our outcome was the formal educational assessment at age 6–7. Binary regression modeling was used to examine residential moves within the three time periods: 0 – <1 year; 1 – <4 years and 4 – <6 years. School moves were examined from age 4 to age 6. We adjusted for demographics, residential moves at different times, school moves and birth related variables. Children who moved home frequently were more likely not to achieve in formal assessments compared with children not moving. Adjusted odds ratios were significant for 3 or more moves within the time period 1 –<4 years and for any number of residential moves within the time period 4–<6 years. There was a dose response relationship, with increased odds ratios with increased frequency of residential moves (2 or more moves at 4–<6 years, adjusted odds ratio 1.16 (1.03, 1.29). The most marked effect was seen with frequent school moves where 2 or more moves resulted in an adjusted odds ratio of 2.33 (1.82, 2.98). This is the first study to examine the relationship between residential and school moves in early childhood and the effect on educational attainment. Children experiencing frequent mobility may be disadvantaged and should be closely monitored. Additional educational support services should be afforded to children, particularly those who frequently change school, in order to help them achieve the expected educational standards.